New South Wales Australia 1:50 000 topographic series. 9139-II & III,. Ashford - Central Mapping Authority of New South Wales (Bathurst, N.S.W. : C.M.A., 1979)
Shows topographic, cadastral and local government information. Also shows type of roads, surfaces and ground conditions.
Monthly and annual rainfall and temperature graphs.
Keywords: Ashford (N.S.W.) -- Maps; Topographic maps